2016
DOI: 10.1016/j.cvfa.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Information Obtained from Diagnosis of Pregnancy Status of Beef Herds

Abstract: Good reproductive efficiency is critical for economic sustainability of beef herds. Standard measurements of reproductive success are the percentage of cows exposed to bulls at the start of the breeding season that are pregnant at midgestation and the percentage of pregnant cows that give birth to a live calf. Converting fetal age data to a reproductive profile displaying pregnancy percentages by 21-day periods provides information for the diagnosis of suboptimal reproductive efficiency and guides intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Reproductive management, particularly data recording of breeding events, was significantly associated with CR, aligning with expert opinions and previous study (Larson & White, 2016). This study identified a negative correlation between synchronization hormone usage and CR, contrasting with previous findings highlighting its benefits (Johnson & Day, 2004;Mialot et al, 2003;Thomas et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…Reproductive management, particularly data recording of breeding events, was significantly associated with CR, aligning with expert opinions and previous study (Larson & White, 2016). This study identified a negative correlation between synchronization hormone usage and CR, contrasting with previous findings highlighting its benefits (Johnson & Day, 2004;Mialot et al, 2003;Thomas et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…Established, controlled breeding seasons for a herd increases productivity compared to long or year-around breeding seasons [22]. Analyzing the herd reproductive data from a single breeding season in 21-day intervals allows for an overall assessment of the herd to determine differences in reproductive success between 21-day intervals as the breeding season progresses compared to desired patterns [23]. Analyzing the percent of calves being born over these intervals serves as a method to evaluate herd-level reproductive efficiency, but does not assess the reproductive efficiency of individual bulls.…”
Section: Discussionmentioning
confidence: 99%
“…To be included, fetal age estimation had to be collected in a manner that allowed categorizing individual cows into 20-or 21-day intervals. 4,5,6,7 If a herd was presented with fetal age estimated by month or trimester, the entire herd was excluded. The initial dataset included 625 herds with pregnancy diagnosis staged into 20-or 21-day intervals.…”
Section: Herd Descriptionmentioning
confidence: 99%